Regulation of Sulfate Uptake by Amino Acids in Cultured Tobacco Cells - Hart, James W. (1969)
The sulfur requirements of tobacco (Nicotiana tabacum L. var. Xanthi) XD cells grown in chemically defined liquid media can be satisfied by sulfate, thiosulfate, l-cyst(e)ine, l-methionine or glutathione, and somewhat less effectively by d-cyst (e) ine, d-methionine or dl-homocyst (e)ine. Sulfate uptake is inhibited after a 2 hr lag by l-cyst (e)ine, l-methionine, l-homocyst(e)ine or l-isoleucine, but not by any of the other protein amino acids, nor by d-cyst(e)ine. l-cyst(e)ine is neither a competitive nor a non-competitive inhibitor of sulfate uptake. Its action most closely resembles apparent uncompetitive inhibition. Inhibition of sulfate uptake by l-cyst(e)ine can be partially prevented by equimolar l-arginine, l-lysine, l-leucine, l-phenylalanine, l-tyrosine or l-tryptophan, but is little affected by any of the other protein amino acids. The effective amino acids are apparent competitive inhibitors of l-cyst(e)ine uptake after a 2 hr lag. Inhibition of sulfate uptake by l-methionine cannot be prevented, nor can uptake of l-methionine be inhibited by any single protein amino acid. The results suggest the occurrence of negative feedback control of sulfate assimilation by the end products, the sulfur amino acids, in cultured tobacco cells.